2022
DOI: 10.1136/rapm-2022-103493
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hypnosis versus enhanced standard of care on postoperative opioid use after total knee arthroplasty: the HYPNO-TKA randomized clinical trial

Abstract: BackgroundHypnosis decreases perioperative pain and has opioid-sparing potential but has not been rigorously studied in knee arthroplasty. This trial investigates the impact of perioperative hypnosis on inpatient opioid use following total knee arthroplasty.MethodsThis prospective randomized controlled trial was conducted at a single academic medical center. The hypnosis arm underwent a scripted 10 min hypnosis session prior to surgery and had access to the recorded script. The control arm received hypnosis ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…Another trial (N = 64) reported that hypnosis, which shares some characteristics of relaxing virtual reality, 5 reduces opioid use. 22 Previous virtual reality trials used sessions that lasted between 3 5 and 15 minutes, 4 usually 1 session per day. 23 The duration and frequency of the sessions in our study were thus within the range of previous studies and practical for hospitalized patients.…”
Section: Discussionmentioning
confidence: 99%
“…Another trial (N = 64) reported that hypnosis, which shares some characteristics of relaxing virtual reality, 5 reduces opioid use. 22 Previous virtual reality trials used sessions that lasted between 3 5 and 15 minutes, 4 usually 1 session per day. 23 The duration and frequency of the sessions in our study were thus within the range of previous studies and practical for hospitalized patients.…”
Section: Discussionmentioning
confidence: 99%
“…A caring relationship releases endogenous opiates in patients as outlined in Jaak Panksepps's ‘brain opioid hypothesis of social relations’ [ 57 ]. This moderates adrenergic stress reactions, engaging mu-receptors for further pain reduction [ 58 ▪ ]. ‘Mind–body therapies’ (hypnosis, meditation, cognitive–behavioural therapy, guided imagery, etc.)…”
Section: Practical Thoughts On Multimodal General Anaesthesia For Cli...mentioning
confidence: 99%
“…In a randomised, controlled trial, patients undergoing total knee arthroplasty received either a 10 min in-person hypnosis session and access to a recording PLUS hypnosis education (treatment group), or hypnosis education alone (control group), to study the impact of hypnosis on postoperative inpatient opioid use 1. In the hypnosis treatment group (n=31), patients used mean (SD) 70.5 (48.4) oral morphine equivalents per 24 hours of admission (OME/24 hours) versus 90.7 (74.4) OME/24 hours in the education only control group (n=33), a difference that was not statistically significant.…”
mentioning
confidence: 99%